A Petersen Type ‘M’ Sword in the Naval Academy’s Collections: Viking History Meets the Modern Navy - Fitzgerald, Jill (The Northern Mariner / Le marin du nord, 2024)
Sometime between 850-950 CE a 91cm single-edged sword was forged in Viking Age Norway. Eventually, that sword was placed in the earth, likely buried alongside its owner. Roughly 1,000 years later (in 1957), that sword was presented to the brigade of midshipmen at the United States Naval Academy by President Eisenhower. The artifact has the distinction of being the oldest weapon in the Naval Academy’s possession. This essay considers what forensic and archaeological evidence can tell us about the sword’s hitherto unknown history and also explores this artifact’s modern provenance and connection to US-Norwegian maritime relations in the mid-twentieth century. Entre 850 et 950 EC, une épée à un tranchant de 91 cm a été forgée dans la Norvège de l’ère des Vikings, puis elle a été enterrée, probablement aux côtés de son propriétaire. Environ 1 000 ans plus tard (en 1957), le président Eisenhower a présenté l’épée à la brigade d’aspirants de marine à l’Académie navale des États-Unis. L’artéfact a la particularité d’être la plus ancienne arme en la possession de l’Académie navale. Le présent article traite de ce que les preuves médico-légales et archéologiques peuvent nous dire au sujet de l’histoire jusqu’ici inconnue de l’épée et examine la provenance moderne de cet artéfact ainsi que son rapport aux relations maritimes américano-norvégiennes au milieu du 20e siècle.